Chemistry and cytotoxic activity of essential oil from the stem bark of Calophyllum soulattri - Mah, Siau Hui; Ee, Gwendoline Cheng Lian; Teh, Soek Sin (Chemic Publishing Company, 2013)
GCMS analysis of the essential oil from the stem bark of Calophyllum soulattri detected twenty components. Allo-aromadendrene was present as the most abundant component. Two other major constituents are α-gurjunene and β-eudesmene. The volatile oil exhibited moderate cytotoxicity against SNU-1, Hep G2, NCI-H23, K562, Raji, IMR-32 and SK-MEL-28 cells.